K. Kucarov. Bulgarian lexeme classes and the studying of part of speech classes (Contrastive Linguistics, 2024)
Константин Куцаров. Българските лексемни класове и учението за частите на речта. София: ИК „Колибри“, 2022, 350 с. ISBN 978-619-02-1031-3.The review is focused on the innovative ideas and findings in the monograph by K. Kucarov: the contemporary view of the classification of lexemes into part-of-speech-classes and the highlighting of the categories discursive and determinative; novel interpretations of some verbal categories and their grammemes in Bulgarian.